An Analysis On English Vocabulary Used In Jawa Pos - Wahyuni, Ika (2004)
This research is about English vocabulary used in the Jawa Pos. It is focussing on the ways of using English vocabulary and the reasons of using English Vocabulary in Jawa Pos. The objective of this research is to describe the ways of English vocabulary used in Jawa Pos and to find out the reasons of its use. This research is a descriptive research. In this study, the researcher uses random sampling method to collect the data. The researcher collects and reads the newspaper to find the sentences that use English vocabulary and take them as the primary data. The researcher classifies them into their categories of use and analyzes the reasons of the use using Dell Hyme's Theory. The result of this research shows that there are : 1). The ways of using English vocabulary in Jawa Pos, such as bold type, italic, mixing English vocabulary with Indonesian prefix, and writing English vocabulary and its Indonesian translation 2). The forms and parts of speech, such as the original borrowings, borrowings word by translation, and parts of speech (noun, verb, adjective, hybrid, idiom, noun phrase, verb phrase, adjective phrase, and compound noun) 3).The reasons of using English vocabulary, such as to make the readers certain in order to understand the term exactly, the purpose is not very clear yet, and need filling motive (there is no an exact term in Indonesian language, the terms are commonly used and familiar in society, and the title of book, magazine, conference, and newspaper).